Brian Shorland: Doyen of New Zealand Science - Gregory, Geoff (New Zealand Science Review, 2014)
​After an uninspired schooling, in which the only thing he excelled at was Latin (although he did eventually matriculate), and a brief spell in a boring job as an accounts assistant, Brian Shorland was urged by his sister Jessie to join the Agricultural Chemistry Laboratory in Wellington as a cadet in order to attend day-release classes at university. Work in the laboratory was a revelation for him, and a stimulus to start on an all-absorbing, prestigious career in biochemistry, which earned him international recognition and the accolade from then President of the Royal Society of New Zealand, Trevor Hatherton, that he was the ‘doyen of working scientists in New Zealand’. Dr Joan Cameron (née Mattingley), a former President of the New Zealand Association of Scientists, has combined information from interviews with Dr Shorland before his death in 1999 and from his family members and work associates, with Brian’s published work, and compiled a fascinating biography of this brilliant and complex man. Now in poor health, she has latterly received considerable editorial support in this by Emeritus Professors Neil Curtis and Brian Halton, who have piloted the book through to publication.